2020
DOI: 10.1371/journal.pone.0228136
|View full text |Cite
|
Sign up to set email alerts
|

Towards the implementation of a DNA barcode library for the identification of Peruvian species of Anastrepha (Diptera: Tephritidae)

Abstract: The genus Anastrepha is a diverse lineage of fruit-damaging tephritid flies widespread across the Neotropical Region. Accurate taxonomic identification of these flies is therefore of paramount importance in agricultural contexts. DNA barcoding libraries are molecularbased tools based on a short sequence of the mitochondrial COI gene enabling rapid taxonomic identification of biological species. In this study, we evaluate the utility of this method for species identification of Peruvian species of Anastrepha an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Distribution.— Anastrepha nolazcoae is known only from Peru (Amazonas, Cajamarca, Huánuco, San Martín, Madre de Dios) (Norrbom and Korytkowski 2011, Barr et al 2017, Bartolini et al 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Distribution.— Anastrepha nolazcoae is known only from Peru (Amazonas, Cajamarca, Huánuco, San Martín, Madre de Dios) (Norrbom and Korytkowski 2011, Barr et al 2017, Bartolini et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The larvae fed on the fleshy part of the seed chamber and the seeds (Figs. 117,118) (Norrbom and Korytkowski 2011, Bartolini et al 2020.…”
Section: Anastrepha Coronilli Carrejo and Gonzálezmentioning
confidence: 99%
“…BINs were used to represent species. Several studies have found strong correlation between BINs and species in Diptera (Bartolini et al, 2020, Hernandez-Triana et al, 2017, Yu et al, 2020. For example, when Bartolini et al (2020), sorted morphological Anastrepha (Diptera: Tephritidae) species into BINs, they created 14 BINs for the 16 species represented.…”
Section: Filtering the Data (Module 3)mentioning
confidence: 99%
“…Several studies have found strong correlation between BINs and species in Diptera (Bartolini et al, 2020, Hernandez-Triana et al, 2017, Yu et al, 2020. For example, when Bartolini et al (2020), sorted morphological Anastrepha (Diptera: Tephritidae) species into BINs, they created 14 BINs for the 16 species represented. Hernandez-Triana et al (2017) created 29 BINs for 28 Simuliidae species, and Yu et al (2020) sorted 5 Chironomidae species into seven BINs.…”
Section: Filtering the Data (Module 3)mentioning
confidence: 99%
“…Distribution. Anastrepha nolazcoae is known only from Peru (Amazonas, Cajamarca, Huánuco, San Martín) (Norrbom and Korytkowski 2011;Barr et al 2017;Bartolini et al 2020).…”
Section: Anastrepha Nolazcoaementioning
confidence: 99%